Early Postoperative Use of Diuretics After Kidney Transplantation Showed Increase in Delayed Graft Function. (June 2020) - Baar, Wolfgang; Kaufmann, Kai; Silbach, Kai; Jaenigen, Bernd; Pisarski, Przemyslaw; Goebel, Ulrich; Kalbhenn, Johannes; Heinrich, Sebastian; Knoerlein, Julian
Purpose: In acute renal injury, diuretics are widely considered to be harmful. Nevertheless, they are used frequently after kidney transplantation. We hypothesized that diuretics administered in the early postoperative treatment after kidney transplantation increase the incidence of delayed graft function (DGF). Methods: In this monocentric, retrospective cohort analysis, we screened the closed files of all consecutive patients who underwent kidney transplantation from 2011 to 2017. The outcome variable was DGF, defined as at least 1 hemodialysis within 7 days postoperatively. To stratify for baseline characteristics such as waiting time or cold ischemic period, we employed a propensity score-matched analysis. Further statistical processing included basic descriptive statistics, Mann-Whitney U test, and binary logistic regression analysis. Results: The unmatched cohort included 445 patients and showed a significantly increased rate of DGF for patients who received either furosemide or mannitol or a combination of both (5% vs 25%; P < .001). Mannitol (odds ratio [OR]: 4.094) and furosemide (OR: 2.915) showed a significant correlation with DGF in the multivariate regression analysis. Propensity score-based matching resulted in a matched cohort of 214 patients with balanced baseline risk variables. In this matched cohort, the rate of DGF was significantly increased in patients who received diuretics in the early postoperative treatment (7% vs 16%; P = .031). Conclusion: Our results show that postoperatively administered diuretics are associated with an increased rate of DGF even in a cohort with balanced preoperative risk variables. This study supports recently published reviews, which call diuretics in the transplantation process into question.